Pengalaman Mahasiswa Bimbingan Konseling dalam Menghadapi Quarter Life Crisis : Studi Fenomenologi - Srinikasari, Ariska; Pratama, Farhan Fajar; Selvia, Nia (Jurnal Dimamu, 2025)
Quarter Life Crisis (QLC) is an emotional crisis condition often experienced by final-year students during the transition phase to early adulthood. This study aims to deeply understand this experience. Using a qualitative approach with a phenomenological design, this study explored the subjective experiences of five final-year students from the Guidance and Counseling Study Program at IAIN Kerinci, selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using the interactive model of Miles and Huberman. The results revealed that QLC is characterized by uncertainty about the future, intense social pressure, emotional disturbances, and a profound self-reflection process. The main triggers include psychological unpreparedness as an internal aspect and family expectations as an external factor. Students attempt to overcome QLC through social support, spiritual approaches, and other adaptation strategies. This study concludes that QLC is a significant and complex developmental phenomenon in the psychosocial journey of students, requiring structured support from the academic environment through adaptive and stigma-free counseling services.